Effects of Instructional Materials on the Academic Performance of Learners in Selected Primary Schools in Kabale Municipality. - Turyakira, Josephat (2024)
The study examined the effects of instructional materials on the academic performance of learners in selected primary schools in Kabale Municipality. The study was carried out in three randomly selected primary schools in Kabale Municipality, the study objectives were; to explore the views of teachers and learners on the extent to which instructional facilities affect student performance, to examine the challenges that learners in primary schools face in accessing instructional materials, to assess the strategies that teachers use to minimize the challenges of attaining and using quality instructional materials. The researcher used descriptive survey designs in collecting the data. A descriptive survey design was used in collecting the data to describe schools and respondents in the study schools. A total sample of 100 respondents was selected to participate in the study. The researcher used both questionnaires and interview guides in collecting the necessary data about the topic. The data collected was analyzed by using both qualitative and quantitative techniques and presented in tables, frequencies, and percentages. In the findings, the challenges were discussed in terms of their potential impact on student performance and academic achievement. The researcher concluded that efforts should be made to improve infrastructure in primary schools, including providing reliable electricity, internet connectivity, and appropriate storage facilities for instructional materials. The researcher recommended that policymakers and education authorities should prioritize allocating sufficient funds to primary schools to ensure adequate access to instructional materials. This includes budgets for purchasing textbooks, technology, and other resources essential for effective teaching and learning.